2020
DOI: 10.3733/ca.2020a0015
|View full text |Cite
|
Sign up to set email alerts
|

Supporting evidence varies for rangeland management practices that seek to improve soil properties and forage production in California

Abstract: California is increasingly investing in policies and programs that promote soil stewardship on natural and working lands as a way to help achieve multiple goals, including improved forage production and climate change mitigation. To inform the growing expectations for rangeland management activities to promote such services, we conducted an evidence synthesis assessing how four commonly suggested practices (silvopasture, prescribed grazing, compost application and riparian restoration) affect a suite of soil p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…In California grasslands, the amount of carbon uptake and whether a particular site is a net carbon source or sink can vary interannually, largely due to variability in annual rainfall [23][24][25]. Cattle grazing may affect soil carbon storage in California grasslands, though any effects appear specific to site characteristics and grazing regime [26][27][28].…”
Section: Cattle Grazing Wildfire and The Carbon Cycle On California R...mentioning
confidence: 99%
See 1 more Smart Citation
“…In California grasslands, the amount of carbon uptake and whether a particular site is a net carbon source or sink can vary interannually, largely due to variability in annual rainfall [23][24][25]. Cattle grazing may affect soil carbon storage in California grasslands, though any effects appear specific to site characteristics and grazing regime [26][27][28].…”
Section: Cattle Grazing Wildfire and The Carbon Cycle On California R...mentioning
confidence: 99%
“…However, the accumulation of aboveground biomass in shrublands results in the storage of atmospheric carbon. Therefore, unlike grasslands, where research has shown mixed or uncertain results from the effect of grazing management on ecosystem carbon storage [23,[26][27][28]67], rangelands that experience shrub encroachment in the absence of grazing will accumulate aboveground carbon up to some point determined by the shrub type, ecosystem constraints, or major disturbances (such as wildfires).…”
Section: Shrub/grass Dynamicsmentioning
confidence: 99%
“…Compensating landowners for soil carbon through PES markets generally depends on additionality, with the exception of programs that compensate landowners for existing soil carbon or avoided grassland conversion. For markets that require measurable augmentation of soil carbon, additionality can be difficult to ensure on semiarid and arid rangelands because of their nonequilibrium nature (Westoby et al 1989, Vetter 2005, Booker et al 2013, with variable outcomes depending on local edaphic and climatic characteristics (Carey et al 2020). California's rangelands are notable in their heterogeneity and spatial variability, ranging from arid inland valleys to mesic grasslands along the coast (Vetter 2005, Huntsinger and Bartolome 2014, Sloat et al 2018).…”
Section: Pes Market Incentivesmentioning
confidence: 99%